ChemInform Abstract: Alkylations and Hydroxymethylations of Pyrazines via Green Minisci‐Type Reactions. Issue 48 (2nd December 2014) - Bohman, Bjorn; Berntsson, Benjamin; Dixon, Ruby C. M.; Stewart, Craig D.; Barrow, Russell A.
Abstract A new general access to (hydroxymethyl)trialkylpyrazines utilizing Minisci‐type chemistry is developed.